The prospects of cold ironing as an emissions reduction option - Zis, Thalis (My University, 2019)
Maritime shipping is considered the most fuel efficient mode of transport with the lowest contribution in CO2 emissions. However, the sector has seen increasing pressure to improve its environmental performance, particularly when it comes to SOx, NOx, and PM emission pollutants. The majority of academic literature is focusing on the full journey environmental aspects of maritime transport, and less attention is given to ports. Davarzani et al. (2016) conduct a literature review on greening ports in order to identify research areas for further investigation (1). Cold ironing is the process of providing shorepower to cover the energy demands of vessels calling at ports. In California six ports are included to the At-Berth regulation that constitutes mandatory the use of the technology for ocean going vessels (70% of total vessel calls, up to 80% by 2020). The EU regulation on at-berth emissions is targeting only SO2 emissions, the reduction of which is also the objective of Emission Control Ares (ECAs). Therefore, a ship can switch to ultra-low sulfur fuel while at berth or within ECAs, or alternatively use scrubber systems to comply with the regulation (2). The scrubber solution reduces PM emissions as well, but has a limited effect on NOx. A paradox is evident; between 2005 and 2015 (the sulfur limit was 1% within ECA, 0.1% at berth) a vessel calling at EU ports would have a higher incentive to invest in cold ironing as it would replace the use of ultra-low sulfur fuel at the port. The objective of the paper is to start a discussion on the future prospects of cold ironing as a viable option to reduce in port emissions, as well as to present a quantitative framework that can be useful to stakeholders deciding on whether to invest in this technology or not.